The life experiences of therapists who are mothers to children with developmental disability. - Packery-Babamia, Sumaya (My University, 2010)
Working mothers who care for a child with disability are subject to very high stress levels. Not only do they have to cope with the ordinary stresses of motherhood but also the additional care-giving and financial implications that disability brings about. Working requires that they balance family and occupational demands. Speechlanguage therapists, occupational therapists and physiotherapists are professionals who work specifically in the field of disability. The literature indicates that the nature of their work predisposes them to decreased psychological well-being and higher stress levels, resulting in poor professional longevity. Subsequently, working therapists who mother children with developmental disabilities are unique in that they may be subject to the stress levels within each social role which they occupy. An account of their personal experiences provides insight into personal and professional coping mechanisms utilised to manage stress and burnout. The objectives of the study were qualitatively embedded within the Interpretative Phenomenological Analysis research design. Eight therapists were recruited and participated in an imagery task as well as a discursive interview. A three phase method of data collection was implemented. The raw data was coded graphically as well as through transcriptions of the interviews. Data analysis entailed merging of images, transcripts and field notes. The data were analysed thematically as well as via keywords and cognitive maps. The results indicated that the role as a mother to a child with developmental disability had a significant impact on them. Therapist mothers engaged in multiple roles which presented with intrinsic benefits. However, this also predisposed them to high levels of stress. They managed these stresses through self-directed cognitive strategies, work and support structures. It appears that these coping mechanisms are superficial and do not address the cause of the stressors. In addition, the bidirectional merging of professional and personal identities often exacerbated the situation. This affected the quality of their personal lives with possible negative repercussions on professional and ethical behaviour. This study calls for a better understanding of personal-professional issues as well as better supportive measures to be in place so that professional well-being is ensured.